APLIKASI ROF TOTAL VARIATION MENGGUNAKAN SPLIT BREGMAN UNTUK MENGURANGI NOISE PADA GAMBAR PEMBULUH DARAH KAPILER DALAM JARI MANUSIA - Mochammad Hafiizh; Vita Kusumasari; Defri Ahmad (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2020)
An image might have noises that could lose important information on that image. As a consequence, we need a consistent method to reduce the noise without erasing the important information. In this paper, ROF Total Variation using Split Bregman is applied to the image to reduce the noise. We choose the monochrome image of the human capillaries on the fingertips.